Engaging youth voices to address racial disproportionality in schools: Exploring the practice and potential of youth participatory research in an urban district. (March 2021) - Richards-Schuster, Katie; Wernick, Laura J.; Henderson, Maren; Bakko, Matthew; Rodriguez, Miguel A.; Moore, Eric
Highlights: Presents a case study of youth participatory research in an urban school district. Conceptualizes youth participatory research as tool for informing school policies. Explore the tensions of youth participatory research in a school district. Discusses navigating power, racial injustice, youth voice and adult roles in schools. Offers practical suggestions for school interested in youth participatory research. Abstract: Drawing upon a large district-wide initiative to systematically use youth participatory research in all middle and high schools as a way to address the racial disproportionality in school experience and disciplinary actions, this paper conceptualizes youth participatory research as a tool to bring youth voices to inform school climate and school policies. The program, which began in 2015, has involved teams from 31 middle and high schools from across the district to use youth participatory evaluation to examine school climate, racial disproportionality, discipline issues, and student and teacher relationships, among other issues. This paper is a result of a multi-year, ongoing research-practitioner partnership focused on continuous program improvement and reflection. In the paper, we draw upon learning from the first five years to conceptualize a multi-level, iterative change model that highlights navigating tensions and challenges such as power, racial injustice, and authentic youth voice within a school district. We reflect on the learning to date and explore the implications for engaging youth participatory research practices within school districts. These critical reflections include the: 1) importance of engaging the most impacted youth, 2) need to prepare stakeholders for research, 3) critical nature of centering race and racial injustice within youth participatory research, 4) requirement of adapting to the realities of students' lives, school priorities and time; 5) attention focused on the role of adults as advisors within youth participatory research efforts; and the 6) need for adult stakeholders to listen to youth's findings. We close with practical lessons and future directions for youth participatory research to impact systemic change within large school districts.